Evaluation of Biofertilizers and Biochar on the Plant Growth and Productivity of Soybean (Glycine max) - Ramawat, Naleeni; Bukke, Dinesh; Thakur, Deepshikha; Atluri, Saiteja (Sciencedomain International, 2021)
The field experiment was conducted in Organic farm of Amity university Noida, Uttar Pradesh, during the kharif season, to evaluate the sole and conjoint effect of biofertilizers and biochar on the yield, growth and productivity of Soybean (Glycine max). The five treatments viz. T1 (Control), T2 (Biochar), T3 (Biochar + Rhizobium), T4 (Biochar + Azospirillum) and T5 (Biochar + Rhizobium + Azospirillum) were used. Plant growth parameters like shoot length, root length, number of leaves, pod length, pod girth, plant height, crop yield and soil parameters were observed for the effect of various treatments. Among the all treatments the treatment T3 (Biochar with Rhizobium) maximum shoot length (52.30), root length (17.30) followed by T4 (Biochar + Azospirillum) and plant productive are maximum mean of number of pods was recorded in T3 (Biochar + Rhizobium) i.e. 32.6, whereas minimum (30.1) was recorded in T1(control) followed by T4(Biochar + Azospirillum) i.e.32.41, T5 (Biochar + Rhizobium + Azospirillum) i.e. 31.05 and T2 (Biochar) i.e.31.31   has shown significant effect on plant growth characters and plant yield. These results indicate that the   conjoint use of biochar and Rhizobium have potential to enhance the crop performance and simultaneously improves the soil properties for sustainable farming without reliance on synthetic agrochemicals.
Keywords: 2. Zero hunger; 15. Life on land; 6. Clean water